2022
DOI: 10.33024/mnj.v4i5.6348
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Antara Usia, Jenis Kelamin, Mobilitas, Dan Pengetahuan Dengan Kejadian Demam Berdarah Dengue Di Wulauan, Kabupaten Minahasa

Abstract: Dengue Hemorrhagic Fever (DHF) is a viral infection transmitted through the bite of the Aedes aegypti mosquito. Factors that can influence the incidence of DHF include the low immunity status of community members and the population density of transmitting mosquitoes because there are many breeding places for mosquitoes. Age, gender, mobility, and knowledge are also risk factors for the incidence of DHF. DHF cases have increased over the past five years, with the epidemic recurring. DHF cases in Indonesia in 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
1
4
0
5
Order By: Relevance
“…According to Siregar (Baitanu et al, 2022), this indicates that knowledge or cognitive aspects related to DHF eradication are crucial domains in shaping an individual's overt behavior. Without knowledge, individuals lack the basis for making decisions and taking actions to address the challenges they face.…”
Section: Resultsmentioning
confidence: 99%
“…According to Siregar (Baitanu et al, 2022), this indicates that knowledge or cognitive aspects related to DHF eradication are crucial domains in shaping an individual's overt behavior. Without knowledge, individuals lack the basis for making decisions and taking actions to address the challenges they face.…”
Section: Resultsmentioning
confidence: 99%
“…Increasing age is associated with increased maturity, both in terms of cognitive development and professional behavior. Individuals are more likely to place their trust in those who display a higher level of maturity compared to those who lack such qualities (Baitanu, Masihin, Rustan, Siregar, & Aiba, 2022). Age is a significant determinant of vulnerability to dengue virus infection in the context of DHF.…”
Section: Discussionmentioning
confidence: 99%
“…Other research, however, found no significant link between sex and DHF incidence in Wulauan, Minahasa Regency (Baitanu et al 2022). According to Malaysian research (Azami et al, 2011), gender has no effect on DHF.…”
Section: Distribution Of Dhf Cases In 2021-2022 By Personmentioning
confidence: 93%